Features of heart rate variability in hockey players aged 15-16 years in sports training - Surina-Marysheva, E.; Erlikh, V.; Krivokhizhina, L.; Marchenko, K.; Kantyukov, S. (Journal of Physical Education and Sport, 2019)
The article aims to identify the features of heart rate variability in elite hockey players aged 15-16 years(n = 36) in the annual training cycle. Heart rate variability was studied in the preparatory and competitive preparation periods (July-December-February). The comparison group consisted of students of a college of physical education of a similar age (examination time: February). In the work, standard methods for assessing HRV at rest (time domain and spectral analysis method) were used. The reactivity coefficient of the parasympathetic system (30: 15) in response to orthostasis was calculated. By the middle of the competitive period, VLF waves decrease; HF waves increase from 34% to 43% and there is a decrease in VLF waves. The ratio of the power of spectral waves changes from LF <HF <VLF to LF <VLF <HF. All changes in HRV indicators are preserved until the end of the competitive period. The value of 30: 15 remains stably low throughout the observation period. Relative to students with high motor activity, hockey players aged 15-16 years have the reduced values of LF (ms2), LF%, LF / HF 30:15 (hockey players: M ± m = 1.31 ± 0.04; 0.21; physically active students: M ± m = 1.51 ± 0.05; SD = 0.18 (p <0.001); increased RMSSD and HF%. In the competitive period in elite hockey players, the vagal effect on the rhythm of the heart increases, which helps to increase the efficiency of the heart at rest.The power of the higher subcortical centers of the autonomic system remains unchanged and corresponds to the age of the sample. The increased power of the higher subcortical structures of the autonomic system on heart rate regulation is due to the features of the pubertal period.In response to orthostasis, heart rate regulation is not yet perfect, which may be a consequence of exposure to irrational physical exertion. Key Words:heart rate variability, athletes, puberty, hockey Intr